2017
DOI: 10.1039/c7ob02149f
|View full text |Cite
|
Sign up to set email alerts
|

Controlling charge-transfer properties through a microwave-assisted mono- or bis-annulation of dialkynyl-N-(het)arylpyrroles

Abstract: A selective microwave-assisted mono- and bis-annulation of dialkynyl-N-(het)arylpyrrole derivatives is described. These polycyclic aromatic hydrocarbons (PAHs) have been photophysically and computationally characterized. The mono-annulated systems display interesting charge-transfer properties. By contrast, these properties vanish within the more conjugated bis-annulated compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 36 publications
0
35
0
Order By: Relevance
“…Furthermore, we can observe that the low-lying absorption band of most of the compounds (apart compounds 7 b and 7 d) reported herein displays a vibronic character (similar to azaullazine 4) suggesting a local absorption process as discussed in our previous report. [20] We studied the fluorescence properties of the azaullazine derivatives. While the brominated [20] In the cases of compounds 7 b and 7 d, we can notice that their emission pattern is broad indicating typically a charge transfer character, very likely resulting from the presence of the electron-withdrawing effect of the formyl moieties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we can observe that the low-lying absorption band of most of the compounds (apart compounds 7 b and 7 d) reported herein displays a vibronic character (similar to azaullazine 4) suggesting a local absorption process as discussed in our previous report. [20] We studied the fluorescence properties of the azaullazine derivatives. While the brominated [20] In the cases of compounds 7 b and 7 d, we can notice that their emission pattern is broad indicating typically a charge transfer character, very likely resulting from the presence of the electron-withdrawing effect of the formyl moieties.…”
Section: Resultsmentioning
confidence: 99%
“…[19] Concomitantly, our research group described the mono-and bisannulation of dialkynyl-N-(het)arylpyrroles promoted by InCl 3 under microwave-assisted heating. [20] Along both reports, it was shown that the introduction of the additional nitrogen atom at position 6 within the ullazine backbone (i. e. aza-ullazine) did not induce significant electronic changes in comparison with the parent ullazine core. Indeed, azaullazine and ullazine display similar absorption and emission properties.…”
Section: Introductionmentioning
confidence: 95%
“…Starting dibrominated materials 1a – c were synthesized following our previously reported procedure and were then subjected to Sonogashira cross‐coupling reaction with N , N ‐dibutyl‐4‐ethynylaniline. Reactions were performed under microwave irradiation in the presence of PdCl 2 (PPh 3 ) 2 /CuI catalytic system.…”
Section: Resultsmentioning
confidence: 99%
“…2.1 equiv. of alkyne, 10 mol‐% of PdCl 2 (PPh 3 ) 2 and CuI, 35 mol‐% of PPh 3 in Et 2 NH:DMF (2:1, v:v)] . Only the pyridine derivative 2a was obtained in 46 % yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation